RESEARCHES REGARDING THE INFLUENCE OF THE NUTRITION SPACE AT DRACOCEPHALUM MOLDAVICA L. (DRAGONHEAD) SPECIES CULTIVATED UNDER THE CONDITIONS OF A.R.D.S. SECUIENI - MARGARETA NAIE; OANA MIRZAN; DANIELA-IULIANA DOBREA (Journal of Engineering Studies and Research, 2017)
The present paper presents the results on the influence of the nutrition space at Dracocephalum moldavica L., cultivated under the conditions of A.R.D.S. Secuieni between 2016 and 2017. Following the interaction of the factors, the distance between the rows and the distance between the plants per row was found that in the variant sown at 70 cm between the rows and 15 cm between the plants per row there was an increase in the average number of branches (2,27). The variants sown at 50 cm and 70 cm between the rows achieved deficit production, very significant compared to the control sowing at the 25 cm between the rows.